2020
DOI: 10.1007/s00018-020-03687-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of peroxisomal trafficking and distribution

Abstract: Peroxisomes are organelles that perform a wide range of essential metabolic processes. To ensure that peroxisomes are optimally positioned in the cell, they must be transported by both long- and short-range trafficking events in response to cellular needs. Here, we review our current understanding of the mechanisms by which the cytoskeleton and organelle contact sites alter peroxisomal distribution. Though the focus of the review is peroxisomal transport in mammalian cells, findings from flies and fungi are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 124 publications
(234 reference statements)
0
15
0
Order By: Relevance
“…Adaptor protein complex 2 associated proteins (AP2M1 and CTTN) were identified and indicate a role in cargo internalization via clathrin-mediated endocytosis and actin dynamics [ 65 , 84 ]. Lastly, ERVK IN may interact with Pex14 and Pex13 independently of the main network for peroxisome import [ 63 ]. While these pathways were likely important for the ancestral exogenous ERVK to transverse the cell and mediate infection, it remains unclear how endogenous IN may interact with these systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptor protein complex 2 associated proteins (AP2M1 and CTTN) were identified and indicate a role in cargo internalization via clathrin-mediated endocytosis and actin dynamics [ 65 , 84 ]. Lastly, ERVK IN may interact with Pex14 and Pex13 independently of the main network for peroxisome import [ 63 ]. While these pathways were likely important for the ancestral exogenous ERVK to transverse the cell and mediate infection, it remains unclear how endogenous IN may interact with these systems.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, most betaretroviral IN enzymes contained features related to protein trafficking, such as a Wxxx[FY] motif (aa. 133-137 in ERVK, MMTV, ENTV, and JRSV) that binds Pex13 and Pex14 for peroxisomal import [63], a SxIP motif (aa. [137][138][139][140][141][142][143][144][145][146][147][148][149][150] that binds to EBH domains in end-binding proteins involved in microtubule transport [64], and a tyrosine-based YXXØ sorting signal (aa.…”
Section: Characterization Of Eukaryotic Linear Motifs In Ervk Integrase and Other Betaretroviral Integrasesmentioning
confidence: 99%
“…In the years since, mostly in studies using Drosophila and mammalian cultured cell lines, scientists have found peroxisomal transportation moved along microtubules in a kinesin/dynein dependent manner, (Ally et al, 2009; Kural et al, 2005). However, it remains unclear what physiological factors affect peroxisomal distribution and what are the physiological consequences of different peroxisomal distribution patterns, especially under in vivo conditions(Covill-Cooke et al, 2021). Interestingly, a recent paper showed that some peroxisomes were translocated to lipid droplets and facilitated lipolysis in adult C. elegans and mouse adipocytes, which also suggests that the peroxisome translocation is needed under poor nutrient condition(Kong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PEX11β results in an elongation of the peroxisomal membrane, which is followed by membrane constriction and division resulting in multiple new peroxisomes (Delille et al, 2010;Schrader et al, 2016). Furthermore, lipid flow from the ER at ACBD5-VAP contact sites (Costello et al, 2017;Hua et al, 2017), and pulling forces along microtubules mediated by peroxisomal MIRO1, a membrane adaptor for the microtubule-dependent motor protein kinesin, also contribute to peroxisomal membrane expansion/ elongation (Castro et al, 2018;Covill-Cooke et al, 2021; Figure 1). It has been revealed that besides membrane remodelling and expansion, PEX11β is also involved in the recruitment and assembly of the division machinery, as it interacts with the membrane adaptors FIS1 and MFF at peroxisomes (Koch et al, 2005;Kobayashi et al, 2007;Koch and Brocard, 2012;Itoyama et al, 2013).…”
Section: The Role Of Pex11 In Peroxisome Membrane Dynamicsmentioning
confidence: 99%